Molecular Enhancement of Alfalfa: Improving Quality Traits for Superior Livestock Performance and Reduced Environmental Impact. Issue 1 (1st January 2018) - Singer, Stacy D.; Weselake, Randall J.; Acharya, Surya
ABSTRACT: Forage crops, including grasses and legumes, comprise a critical component of the livestock industry. Although alfalfa ( Medicago sativa L.) is the most widely grown of the perennial leguminous forage species due to a number of positive attributes, it also suffers from various drawbacks related to inefficiencies in rumen fermentation. This results not only in the inferior conversion of plant‐derived nitrogen into milk and meat products, and associated economic losses for producers, but can also lead to serious health issues in livestock and have negative environmental impacts. Therefore, there is currently an impetus for the improvement of traits in alfalfa that could enhance nitrogen and energy use, provide health benefits to the livestock it feeds, and reduce greenhouse gas emissions. Since gains in this area using conventional breeding approaches have proven difficult to achieve, molecular breeding strategies are currently being assessed for their potential to provide a complementary approach. In this review, we examine progress made thus far with regards to improving such quality traits in alfalfa using biotechnological strategies and discuss future priorities and avenues that have the potential to support a sustainable, environmentally friendly, and productive livestock industry.